The tumour necrosis factor receptor family: life or death choices. - Jones, E (2000)
The past twelve months have seen a renewal of interest in the therapeutic potential of members of the tumour necrosis factor receptor family and their cytokine ligands. This biomedical interest has spawned a number of structural studies, which have significantly deepened our understanding of the molecular basis for the function of these cell-surface signalling systems. The fresh data have revealed unexpected mechanisms conferring ligand-receptor specificity and have highlighted the structural requirements for the initiation of intracellular signalling.